Training with independent cranks alters muscle coordination pattern in cyclists - Fernández-Pena, E.; Lucertini, F.; Ditroilo, M. (The Journal of Strength and Conditioning Research, 2009)
In cycling, a circular pedaling action makes the most useful contribution to forward propulsion. Training with independent cranks (IC) has been proposed to improve the pedaling action. The aims of this study were, first, to assess whether the intermuscular coordination pattern of the pedaling action with normal cranks (NC) is modified after a training period with IC and, second, to determine if the new coordination pattern is maintained after a washing-out period. Eighteen cyclists, divided into a control (CG) and an experimental (EG) group, underwent 2 test sessions (T1 and T2) separated by 2 weeks of training (18 hours). The electromyographic (EMG) activity of 4 lower limbs' muscles was recorded while the athletes pedaled at 80 rpm for 60 seconds at 30 and 50% of the maximal power output determined during a maximal pedaling test. The tasks were performed with IC (EG) and NC (EG and CG). The EG underwent a retention test session (T3) after another 18-hour training with NC. EG showed a significant (45.8 ± 8.8 vs. 36.0 ± 6.1%, p < 0.01 at 30% intensity) and a quasi-significant (62.7 ± 10.3 vs. 54.2 ± 8.7%, p = 0.09 at 50% intensity) decrease in vastus lateralis EMG activity and a quasi-significant (36.4 ± 13.4 vs. 43.5 ± 10.9%, p = 0.09 at 30% intensity) and a significant (54.5 ± 12.1 vs. 65.5 ± 16.1%, p < 0.05 at 50% intensity) increase in biceps femoris EMG activity between T1-NC and T2-NC. By T3, EMG activity returned to initial levels (T1). On the contrary, CG did not reveal any significant variation. The results provide scientific support for muscle coordination pattern alteration from the use of IC, potentially achieving a more effective pedaling action. IC training reduces quadriceps exertion, thus preserving it for important moments during competition.